Dolor y nihilismo, una panorámica del sin sentido y el pesimismo en la narrativa latinoamericana (Revista de Crítica Literaria Latinoamericana, 2022)
The recent life standards relegate pain to a medical technique matter. Pharma industry promises to eliminate pain from existence: the hidden story in its advertising speaks of a culture that is dominated by the optimistic imperative, that emboldens the idea that happiness is a sine qua non condition. Such guideline hides the fact that the neoliberal regime exerts personal and collective domination. An example is the boom of consumer and positive literature, texts that consider the reader as a client prototype, a consumer and/or a subject that needs orientation and life lessons. This article proposes a critic towards this kind of literature. Despite of it, it recognizes that, fortunately, Latin-American writing has a prodigious registry of novels where emotional states that are denied today become fertile material to interact with society and accomplish an aesthetic out of it.
Keywords: pain; nihilism; consumer literature; positivity; Latin American literature